2009
DOI: 10.1104/pp.109.136804
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Resources for Maize Cell Wall Biology      

Abstract: Grass species represent a major source of food, feed, and fiber crops and potential feedstocks for biofuel production. Most of the biomass is contributed by cell walls that are distinct in composition from all other flowering plants. Identifying cell wallrelated genes and their functions underpins a fundamental understanding of growth and development in these species. Toward this goal, we are building a knowledge base of the maize (Zea mays) genes involved in cell wall biology, their expression profiles, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(170 citation statements)
references
References 148 publications
(196 reference statements)
6
164
0
Order By: Relevance
“…Mutants with severely modified xyloglucans altered in their ability to be recognized by XETs resulted in loss of tensile strength of the hypocotyl, indicating that the enzyme is necessary to retether the long interstitial xyloglucans during microfibril rearrangment and formation of new partners (Peñ a et al, 2004). Because the xyloglucan endo-b-transglucosylase/hydrolase gene family is quite large in what are considered xyloglucanpoor grass species (Yokoyama et al, 2004;Penning et al, 2009), other substrates were considered for its disproportioning activity that could increase polymer length or make covalently linked heteropolymers (Hrmova et al, 2007). In light of the inability to detect b-glucans in the Golgi membrane, Fincher (2009) Hrmova et al (2007) was catalyzed at quite reasonable rates, it should be noted that those activities were about 1/500 the rate of xyloglucan transglucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants with severely modified xyloglucans altered in their ability to be recognized by XETs resulted in loss of tensile strength of the hypocotyl, indicating that the enzyme is necessary to retether the long interstitial xyloglucans during microfibril rearrangment and formation of new partners (Peñ a et al, 2004). Because the xyloglucan endo-b-transglucosylase/hydrolase gene family is quite large in what are considered xyloglucanpoor grass species (Yokoyama et al, 2004;Penning et al, 2009), other substrates were considered for its disproportioning activity that could increase polymer length or make covalently linked heteropolymers (Hrmova et al, 2007). In light of the inability to detect b-glucans in the Golgi membrane, Fincher (2009) Hrmova et al (2007) was catalyzed at quite reasonable rates, it should be noted that those activities were about 1/500 the rate of xyloglucan transglucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…In some families, a substantially higher number of duplicates were found. For example, all duplicates of the 10 cellulose synthase CesA family members were retained (Penning et al, 2009). Because conventional algorithms only map sequences to unique genes, the high degree of duplication in maize led to an unexpectedly large number of unmapped sequences.…”
Section: Phenotype Variation Can Arise From Differential Expression Omentioning
confidence: 99%
“…Rice snl6 and Arabidopsis irx4 mutants, defective in CCR encoding genes, display altered lignin composition Bart et al 2010). HCT catalyzes generation of p-coumaroyl-CoA from p-coumaric acid and transfer of caffeoyl moiety of caffeoyl-quinate and caffeoyl-shikimate to CoA (Hoffmann et al 2003;Penning et al 2009). …”
Section: Lignin Biosynthesismentioning
confidence: 99%
“…Nucleotide-sugar interconversion pathway Genes involved in nucleotide-sugar interconversion pathway form the basic building blocks of cell wall carbohydrates (Penning et al 2009;Seifert et al 2004). We found that three genes, belonging to each of three groups of C-4 epimerases including GAE-like (UDP-glucuronate-4-epimerase; LOC_Os08g41440), UXE-like (GDP-mannose 4,6-dehydratase; LOC_Os07g04690) and UGE-like (UDPglucose-4-epimerase; LOC_Os09g35800) were up-regulated during cell wall removal (Table 1).…”
Section: Transcriptional Dynamics During Cell Wall Removal and Regenementioning
confidence: 99%